2020
DOI: 10.1080/07853890.2020.1811887
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum virus-specific IgM/IgG antibody in asymptomatic and discharged patients with reoccurring positive COVID-19 nucleic acid test (RPNAT)

Abstract: Ye (2021) Changes in serum virus-specific IgM/IgG antibody in asymptomatic and discharged patients with reoccurring positive COVID-19 nucleic acid test (RPNAT),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Considering the high specificity of the chemiluminescence immunoassay found in previous studies ( Padoan et al, 2020 ) and calculated in our work using NST as the gold standard, these results could indicate the existence of numerous undiagnosed COVID-19 cases among HCWs in the assistant setting; infected people likely remained asymptomatic, which could explain the trouble in identifying these workers through NST ( Liu et al, 2020 ). Moreover, the large difference in positive results between serological and nasopharyngeal tests could indicate many sources of unknown exposure to SARS-CoV-2 despite the implementation of preventive measures.…”
Section: Discussionsupporting
confidence: 56%
“…Considering the high specificity of the chemiluminescence immunoassay found in previous studies ( Padoan et al, 2020 ) and calculated in our work using NST as the gold standard, these results could indicate the existence of numerous undiagnosed COVID-19 cases among HCWs in the assistant setting; infected people likely remained asymptomatic, which could explain the trouble in identifying these workers through NST ( Liu et al, 2020 ). Moreover, the large difference in positive results between serological and nasopharyngeal tests could indicate many sources of unknown exposure to SARS-CoV-2 despite the implementation of preventive measures.…”
Section: Discussionsupporting
confidence: 56%
“…Older RP patients (≥60 years old) were more susceptible to clinical symptoms at readmission Chen et al [83] China Case series 51 30 62 81/1087 9 d positive 72 IgG positive 68 IgM positive Multivariable regression analysis identified elevated serum IL-6, increased lymphocyte counts and CT imaging features of lung consolidation during hospitalization as the independent risk factors of recurrence Yuan et al [100] China Case series 13 7 41·5 20/182 7 d (13 cases) 14 d (7 cases) 14 positive 6 positive 14 IgG positive 10 IgM positive There were no significant differences between the RP group and the NRP group in age, sex, co-morbidities, epidemiological information, initial symptoms, and the level of antibodies, Patients aged under 18 years and those mild and moderately affected showed a higher re-positive rate. The RP group experienced longer hospital stay Zou et al [108] China Case series 30 23 62·19 53/257 4·6 d positive 34 IgG positive19 IgM positive The frequency of recurrently positive RT-PCR results was significantly lower in those with 3 consecutive negative results (5·4%) than in those with only 2 consecutive negative results (20·6%) Liu et al [94] China Case series 4 11 48 15/92 positive …”
Section: Resultsmentioning
confidence: 99%
“…Nineteen studies ( n = 101) [ 16 , 18 , 22 – 25 , 32 , 35 , 36 , 49 – 51 , 59 , 73 , 76 , 97 , 104 , 107 , 115 ] showed that discharged patients had no symptoms when the nucleic acid test was positive. Among 55 studies, 1054 RP patients had symptoms, cough (19·82%) [ 20 , 26 , 29 – 31 , 34 , 38 , 42 , 44 , 49 , 52 , 60 , 62 , 63 , 66 , 67 , 69 , 71 , 74 , 78 , 81 , 83 85 , 88 , 89 , 91 , 94 , 95 , 98 , 101 , 103 , 106 , 108 , 110 , 119 , 121 , 125 , 127 , 130 ] and fever (14·99%) [ 20 , 28 , 29 , 41 , 44 , 46 , 49 , 52 , 67 ,…”
Section: Resultsmentioning
confidence: 99%
“…The literature flow chart ( Figure 1 ) summarizes the results of search and study selection processes ( 7 ). We included 66 observational studies (total n = 16 525): 4 studies estimated population seroprevalence and included a subpopulation with SARS-CoV-2 infection confirmed by RT-PCR, 45 were cross-sectional or cohort studies characterizing the antibody response (that is, antibody types, levels, and durability), and 17 validated the diagnostic performance of 1 or more immunoassays ( 14–45 - 46–77 - 78, 79 ). Supplement Table 3 shows study characteristics.…”
Section: Resultsmentioning
confidence: 99%